Evaluating Based E-Learning Platforms In Nigerian Higher Education: An SEM-PLS Analysis Based On The Delone And Mclean Model - Fadele Ayotunde Alaba; Nasiru Yakubu; Dokun Iwalewa Oluwajana; Adetokunbo Babafemi; Oluchi Adewale (Jurnal Riset Ilmu Teknik, 2025)
The Federal University of Technology Minna (FUT Minna) serves as the case study, representing a technology-focused institution facing post–COVID-19 challenges in digital education delivery. The research investigates how system quality, information quality, and service quality influence use, user satisfaction, and net benefits in an emerging economy context. A quantitative explanatory design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 60 academic staff members through a structured questionnaire based on validated indicators of the DeLone and McLean model. The analysis was performed using SmartPLS 4.0, encompassing outer model validation (convergent validity, reliability) and inner model testing (path coefficients, R², f², and Q²). The results reveal that system quality and service quality significantly influence system use (t = 2.384, p = 0.018; t = 3.617, p = 0.000, respectively), while information quality exerts a weaker effect. User satisfaction emerged as a key mediator linking system quality to perceived net benefits (t = 3.124, p = 0.002). The model explained 26.8% of variance in use, 23.1% in user satisfaction, and 16.6% in net benefit, confirming moderate explanatory power. These findings highlight that e-learning success in Nigerian universities depends not only on technical reliability but also on continuous service responsiveness and user-centered support. The study suggests that higher education institutions in developing economies should prioritize improving system stability, standardizing instructional content, and strengthening technical support to enhance user satisfaction and learning outcomes. Institutional investment in digital literacy and feedback-driven service improvement can maximize the long-term benefits of e-learning systems. This study extends the application of the DeLone and McLean model to a Sub-Saharan African context, providing empirical evidence on e-learning adoption dynamics in resource-constrained environments. The integrated SEM-PLS approach offers a validated framework for assessing e-learning success and guiding strategic digital transformation in higher education.